Multi-omics analysis reveals a protective role of endogenous proline in sheep oocyte vitrification and its therapeutic application - Dilixiati, Airixiati; Zhao, Xi; Aihemaiti, Aikebaier; Li, Weijian; Fan, Chen; Zhao, Guodong; Wusiman, Abulizi; Wang, Xuguang (Frontiers in Cell and Developmental Biology, 2025)
IntroductionVitrification is a rapid-cooling cryopreservation technique for oocytes and a key method in assisted reproductive technology (ART). During vitrification, oocytes are exposed to high concentrations of cryoprotectants, leading to cryoinjury and osmotic stress that impair oocyte quality and subsequent developmental competence in mammals. However, the complex molecular stress responses evoked by vitrification remain poorly understood.MethodsHere, we used sheep oocytes to compare metabolome and transcriptome profiles before and after vitrification.ResultsIntegrated multi-omics revealed a significant accumulation of the osmoprotectant proline in vitrified oocytes. The upregulation of PYCR3, a regulator of proline synthesis, and the downregulation of P4HA1, which controls hydroxylation, collectively increased intracellular proline levels through this pathway. Guided by this finding, we supplemented the vitrification medium with 0.5 M L-proline, which significantly improved oocyte quality after warming. L-proline supplementation markedly increased the survival rates of vitrified oocytes, reduced oxidative stress, improved organelle distribution (spindle, endoplasmic reticulum, and mitochondria), decreased mitochondrial ROS levels, increased the mitochondrial membrane potential, mitigated ATP decline induced by cryopreservation, and maintained calcium homeostasis.ConclusionThese protective effects collectively enhanced the developmental competence of vitrified sheep oocytes.